-25-6k=-5(5+3k)

Simple and best practice solution for -25-6k=-5(5+3k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -25-6k=-5(5+3k) equation:



-25-6k=-5(5+3k)
We move all terms to the left:
-25-6k-(-5(5+3k))=0
We add all the numbers together, and all the variables
-6k-(-5(3k+5))-25=0
We calculate terms in parentheses: -(-5(3k+5)), so:
-5(3k+5)
We multiply parentheses
-15k-25
Back to the equation:
-(-15k-25)
We get rid of parentheses
-6k+15k+25-25=0
We add all the numbers together, and all the variables
9k=0
k=0/9
k=0

See similar equations:

| -40=v/8 | | t/8+91=86 | | 5+1x=6.50+0.50x | | -6(p-4)-5=23-4p | | (–2d)+9=21 | | 4(5x-12)+0.5x=15.2 | | 69=-5x | | 3p+18=3(()+()) | | x/4-x=x/8+12 | | 6p+29=89 | | 2n−5=5 | | -3+4n=7(4+5n) | | |2y-3|=7 | | 2-2r=-7+4-2r+5 | | 3p+18=3(()+() | | -4(8+4b)=40-4b | | 2x+6+3x-11=-9 | | 40+10a=-70 | | x+7/10=3/5 | | r18+7=10 | | -6(y-73)=-66 | | 0=-5m+6m | | t4+6=10 | | 1/4(x+4)=4/3 | | n/3+-8=-5 | | 24=13+x* | | -2+4n=2 | | 22/a=11/12 | | 5(12-3n)=15n+60 | | 75÷k=15 | | 11g-14=6g+16 | | x=-7-2894 |

Equations solver categories